Glycerol Dry Reforming Over Alumina-Supported Nickel Catalysts - Siew, Kah Weng; Cheng, C. K.; Jolius, Gimbun (2013)
In this paper, dry (CO2)-reforming of glycerol, a new reforming route was carried out over alumina (Al2O3)-supported non-promoted and lanthanum-promoted Ni catalysts. Both sets of catalysts were synthesized via wet co-impregnation procedure. The physicochemical characterization of the catalysts showed that the promoted catalysts possessed smaller metal crystallite size, hence higher metal dispersion compared to the virgin Ni/Al2O3 catalyst. This was also corroborated by estimations employing the Scherrer equation. In addition, modeling of gas-solid catalyst interaction from TGA analysis showed that the Order of Reaction model gave the best result with calcination energy ranged from 138 to 141 kJ mol-1 depending on the heating ramp. Preliminary reaction studies at 1023 K showed that glycerol dry reforming successfully produced syngas (H2 and CO mixture) and the catalytic performance was stable for at least 4 h of reaction.